The slithery shakedown - Hecht, Tracey (Hecht, Tracey. Nocturnals., 2018)
Bismark the sugar glider and his friends, Tobin the pangolin and Dawn the red fox, stand together to scare off a snake who would like to make Bismark its lunch snack.